2005
DOI: 10.1038/sj.cdd.4401827
|View full text |Cite
|
Sign up to set email alerts
|

Notch1 confers thymocytes a resistance to GC-induced apoptosis through Deltex1 by blocking the recruitment of p300 to the SRG3 promoter

Abstract: One notable phenotypic change during the differentiation of immature thymocytes into either mature CD4 or CD8 singlepositive lineages is the acquisition of a resistance to glucocorticoid (GC)-induced apoptosis. We have previously reported that SRG3 is critical in determining the sensitivity for the GC-induced apoptosis in developing thymocytes. We report here that Notch signaling downregulates the transcriptional activation of SRG3 through N-box and/or E-box elements on its promoter. RBP-J represses SRG3 trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…The reduced GR expression may be related to elevated expression of Hes1, a transcription factor known to downregulate GR expression [21]. Also, Deltex-1 has been shown to confer GC resistance in thymocytes [22]. The ICN level is unaffected by Dex treatment (Figure 3, panel f).…”
Section: Resultsmentioning
confidence: 99%
“…The reduced GR expression may be related to elevated expression of Hes1, a transcription factor known to downregulate GR expression [21]. Also, Deltex-1 has been shown to confer GC resistance in thymocytes [22]. The ICN level is unaffected by Dex treatment (Figure 3, panel f).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Weng et al [7] have found activated Notch-1 gene in the majority of samples from patients with T-ALL. Notch-1 has been shown to inhibit T-cell receptorinduced apoptosis in mature cells and dexamethasone-mediated apoptosis in thymocytes and to be antiapoptotic in T cells [8,9]. More and more evidence suggests cancers with activated Notch-1 signal are chemo-resistant [10,11].…”
Section: Introductionmentioning
confidence: 97%
“…Indeed, Notch has been shown to regulate apoptosis in a number of mature cell types, including thymocytes, as well as some cancers [10][11][12]. Furthermore, Notch pathway components are re-expressed in exocrine cells after experimentally induced pancreas injury [13,14].…”
Section: Introductionmentioning
confidence: 99%